Losy mienia kulturalnego polskich Żydów w okresie okupacji hitlerowskiej i w pierwszych latach powojennych - Cieślińska-Lobkowicz, Nawojka (Zagłada Żydów. Studia i Materiały, 2010)
The article presents the problem of Jewish cultural property appropriated during the Second World War and attempts at describing the treatment of Jewish cultural property in Poland shortly after the war, i.e. during the first wave of the restitution process. Apart from the few cases of owners regaining the property owned before the war, the author describes appropriation of “nobody’s Judaica” by state administration. It also draws attention to the necessity of research about either appropriated or damaged cultural property of Polish Jews and the post-war attempts to find and restitute it to their rightful owners or heirs.